2018
DOI: 10.1007/s11356-018-2685-8
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of PCDD/Fs in the neighborhood of a hazardous waste incinerator: human health risks

Abstract: In 1996-1998, a wide surveillance program was initiated in the vicinity of a new hazardous waste incinerator (HWI) placed in Constantí (Catalonia, Spain), which started its regular operations in 1999. The program was aimed at assessing the environmental impact of the facility on the surrounding environment, as well as to evaluate the potential risks for the population living in the neighborhood. Since then, among other measurements, the concentrations of polychlorinated dibenzo-p-dioxins and furans (PCDD/Fs) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The monitoring program has been continuously conducted since 1999. While information of the environmental levels of pollutants has been quite recurrent in the last 20 years [20], data on the concentrations of trace elements in the same biomonitors (i.e., hair, blood and autopsy tissues) have been updated every 4-5 years [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring program has been continuously conducted since 1999. While information of the environmental levels of pollutants has been quite recurrent in the last 20 years [20], data on the concentrations of trace elements in the same biomonitors (i.e., hair, blood and autopsy tissues) have been updated every 4-5 years [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure for the analysis of PCDD/Fs and PCBs in environmental samples has been detailed elsewhere [ 17 , 18 , 19 ]. Appropriate 13 C 12 -labeled recovery patterns were added to the sample to check any losses during the analytical process.…”
Section: Methodsmentioning
confidence: 99%
“…In the end, review mentioned possible effect (6) of biases and confounding on most of the study findings. Various studies have not observed any association between PCDD/F from incinerator and adverse health outcomes on (7)(8)(9)(10) environment and health.…”
Section: Agementioning
confidence: 99%